The Reflection of Vocabulary Implementation Through Educational Texting on EFL Learner’s Reading Skill - Behforouz, Behnam; Frumuselu, Anca Daniela (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This paper investigates the efficiency of using text messaging in the EFL reading classroom at the Islamic Azad University-South Tehran Branch, Iran. After the administration of an Oxford Placement Test (OPT), 74 participants who scored one standard deviation above and below the mean were selected. Participants were randomly assigned into two groups, an experimental and a control, each including 37 individuals. The reading part of the Preliminary English Test (PET) was administered as a pretest. The experimental group received 108 words via short messages during 18 sessions. During each session, they received 6 sentences with 6 words in a meaningful context. In contrast, the participants of the control group received traditional instruction. They were given the same structural points through inductive and deductive instruction in the classroom and the words were presented while teaching each unit. After the treatment, the participants in both groups were assigned to do a reading posttest. The results of the ANCOVA revealed no statistically significant difference between the control and the experimental groups regarding their reading scores. Thus, the vocabulary learning via short message did not have any significant effect on Iranian EFL learners' ability to comprehend pre-intermediate level texts.